Factors Underlying Stigmatization of Epilepsy: A Comparative Case Study of Suba and Meru Central Districts, Kenya - Nyakwana, Tiberry D. O.; Simbauni, Jemimah A.; Jowi, James O. (American Scientific Research Journal for Engineering, Technology, and Sciences, 2014)
Epilepsy is the most common neurological disorder known to mankind. It is shrouded in mystery and associated with supernatural forces resulting in social stigma, systematic discrimination and psychological morbidity to the afflicted. The study was carried out in Suba and Meru central districts in Kenya. The Objective of this study is to determine the factors underlying stigmatization of People with Epilepsy (PWE) in Suba and Meru Central Districts and evaluate the social burden associated with epilepsy. A cross-sectional descriptive study involving the use of a 30-item structured questionnaire, Focus Groups Discussion and key informants. Two hundred and twenty-five (225) household heads, twelve focus group discussions and 30 key informants. A total of 225 households interviewed had male preponderance of 140 (62.2%) to 85 females (37.8%).  The level of education for Suba District respondents was higher as 54.3% had secondary and post secondary education compared to 35.2% for Meru Central  District. All respondents (100%) in both study cohorts were aware of epilepsy. Thirty four percent (34%) of Suba respondents had some knowledge about epilepsy compared to eleven percent (11%) in the Meru Central District cohort. Statistical relationship between negative attitude and fear of epilepsy overall was significant (c2 = 43.69354, df=1, p